2015
DOI: 10.2105/ajph.2015.302837
|View full text |Cite
|
Sign up to set email alerts
|

Coverage Gains After the Affordable Care Act Among the Uninsured in Minnesota

Abstract: Targeting outreach, simplifying the enrollment process, focusing on affordability, and continuing funding for in-person assistance will be important in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…To understand why eligible individuals remain uninsured, several studies have explored consumer experiences with the exchange Marketplaces and Medicaid expansion ( 16 , 23 , 24 , 26 , 29 , 30 , 40 , 41 , 74 , 89 ). Similar to the experiences in Massachusetts ( 20 , 66 ), common barriers to enrollment have included perceived cost of coverage ( 16 , 23 , 29 , 30 , 40 ), limited awareness about coverage expansions and eligibility ( 29 , 30 , 40 , 89 ), difficulty navigating the enrollment process ( 16 , 23 , 30 ), and language barriers ( 41 , 89 ); application assistance from navigators has helped to mitigate some of these barriers ( 89 ). Despite enrollment challenges, adults with new Marketplace or Medicaid coverage have reported high satisfaction with their insurance, doctors offered in network, ease of finding doctors, and affordability and access to care, comparable with reports from other insured adults ( 24 , 26 , 74 ).…”
Section: Aca Impacts On Coverage Of Low-income Populationsmentioning
confidence: 99%
“…To understand why eligible individuals remain uninsured, several studies have explored consumer experiences with the exchange Marketplaces and Medicaid expansion ( 16 , 23 , 24 , 26 , 29 , 30 , 40 , 41 , 74 , 89 ). Similar to the experiences in Massachusetts ( 20 , 66 ), common barriers to enrollment have included perceived cost of coverage ( 16 , 23 , 29 , 30 , 40 ), limited awareness about coverage expansions and eligibility ( 29 , 30 , 40 , 89 ), difficulty navigating the enrollment process ( 16 , 23 , 30 ), and language barriers ( 41 , 89 ); application assistance from navigators has helped to mitigate some of these barriers ( 89 ). Despite enrollment challenges, adults with new Marketplace or Medicaid coverage have reported high satisfaction with their insurance, doctors offered in network, ease of finding doctors, and affordability and access to care, comparable with reports from other insured adults ( 24 , 26 , 74 ).…”
Section: Aca Impacts On Coverage Of Low-income Populationsmentioning
confidence: 99%
“…Most of the studies identified [16][17][18][19][20][21][22] individual assistance as a key strategy used by healthcare providers and community-based organizations to help people enroll for health insurance. The terminology used to describe individual assistance varied.…”
Section: Individual Assistancementioning
confidence: 99%
“…Call et al [16] Minnesota (statewide) ▪ Organized outreach events in community centers, places of worship, townhalls. ▪ Collaborated with small business groups and healthcare providers.…”
Section: Community Outreachmentioning
confidence: 99%
See 1 more Smart Citation
“…To augment the marketing efforts, the ACA required that every state Marketplace also establish a navigator program at the 2014 insurance expansion launch. Recent studies outside of Illinois have found that the strongest predictor of an uninsured individual completing the Marketplace application process was receiving help with enrollment from a navigator or application assister, and conclude that support for ongoing funding for this type of work will be important to maintain or increase the gains in insurance rates for those not insured or for those underinsured (Call et al, 2015;Sommers, Maylone, Nguyen, Blendon, & Epstein, 2015).…”
Section: Introductionmentioning
confidence: 99%